Aged care nurses' job control influence satisfaction and mental health. (18th May 2017) - Elliott, Kate‐Ellen J.; Rodwell, John; Martin, Angela J.
Abstract : Background: Relationships exist between aged care nurses' perceptions of psychosocial work characteristics, job satisfaction and mental health, suggesting these characteristics may be important for the management of aged care services. Aim: An expanded demand–control–support model that included justice perceptions was examined to determine its impact on multiple types of psychological and organisational well‐being outcomes (i.e. job satisfaction, psychological distress and depression). Method: Data were collected from a sample of 173 aged care nurses using a self‐report survey and analysed using hierarchical multiple regression. Results: A significant proportion (27–28%) of the variance in aged care nurses' satisfaction, depression and psychological distress was explained by the psychosocial factors included in the model. Job control had the most consistent impact with direct effects on job satisfaction, psychological distress and depression. Informational justice was associated with both psychological distress and depression. Conclusions: Targeting job control may provide the biggest response for nurse managers in aged care, as it is likely to influence nurses' job satisfaction, psychological distress and depression. Implications for nursing management: Facility managers should implement organisational policies and procedures that promote higher levels of control over how nurses perform their work in order to improve nurse well‐being in aged care settings.